The performance of palm coir pith for methylene blue dye removal in textile wastewater - Nur Aliyana, Alihad (2015)
Textile industry contributes a large amount of wastewater in Malaysia. It is also one of main sources that contribute to the water pollution. Hence, proper studies are needed to investigate the low-cost adsorbents used to remove the dye in textile wastewater. In this study, activated carbon, prepared from palm coir pith which is a waste product obtained throughout the extraction of coir fibre from husk were used as adsorbent for the removal of methylene blue. The palm coir pith was treated by using sulphuric acid and pyrolyzed in a muffle furnace for different temperature and times. There are three parameters considered to test the methylene blue which are pH of the methylene blue, adsorbance rate during adsorbing process and duration of the adsorbed substances staying inside the sample. The results show that in term of acidity, PCP that is pyrolyzed for 300 oC in 1 hour gives better improvement analysis which is 37.33% compared to the others while in terms of clarity, the pyrolysis process in 4 hours at 300 oC gives good result compared to the others which is 89.31 %. Hence, it showed that activated carbon of palm coir pith could be used as low-cost alternatives to commercial activated carbon in textile wastewater treatment for the removal of basic dyes.